2018
DOI: 10.1016/j.chom.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

HCV Broadly Neutralizing Antibodies Use a CDRH3 Disulfide Motif to Recognize an E2 Glycoprotein Site that Can Be Targeted for Vaccine Design

Abstract: SUMMARY Hepatitis C virus (HCV) vaccine efforts are hampered by extensive genetic diversity of HCV envelope glycoproteins E1 and E2. Structures of broadly neutralizing antibodies (bNAbs) (e.g., HEPC3, HEPC74) isolated from individuals who spontaneously cleared HCV infection facilitate immunogen design to elicit antibodies against multiple HCV variants. However, challenges in expressing HCV glycoproteins previously limited bNAb-HCV structures to complexes with truncated E2 cores. Here we describe crystal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
210
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(220 citation statements)
references
References 58 publications
9
210
1
Order By: Relevance
“…Binding of the E2 glycoprotein of hepatitis C virus (HCV) to the large extracellular loop of CD81 is a defining event in the entry of HCV [1] and is targeted by multiple broadly neutralising antibodies; thus placing this molecular interaction at the forefront of current HCV vaccine development [2,3]. Whilst the importance of CD81 in HCV entry is well established, the precise details of E2-CD81 interaction have yet to be defined and the molecular determinants of CD81 receptor activity are only partially understood [4].…”
Section: Introductionmentioning
confidence: 99%
“…Binding of the E2 glycoprotein of hepatitis C virus (HCV) to the large extracellular loop of CD81 is a defining event in the entry of HCV [1] and is targeted by multiple broadly neutralising antibodies; thus placing this molecular interaction at the forefront of current HCV vaccine development [2,3]. Whilst the importance of CD81 in HCV entry is well established, the precise details of E2-CD81 interaction have yet to be defined and the molecular determinants of CD81 receptor activity are only partially understood [4].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the infectivity of genotype 1b is not significantly affected by the presence of any hCD81 variant included in this study. We, therefore, compared the HCV E2 amino acid residues, described to contribute to hCD81 binding [36][37][38][39] for the seven HCV genotypes ( Fig S5a). While all the genotypes consistently display large hydrophobic aromatic amino acids in the four critical hCD81-binding regions, the hCD81 SNV-sensitive genotypes harbour an amino acid variation at position 444 in E2 region 4.…”
Section: Hcd81 Variant-expressing Cells Are Differentially Permissivementioning
confidence: 99%
“…6,7 Despite the heuristic appeal of the lock and key model, interactions between antibodies and antigens, particularly paratopes with epitopes, are far more complex than the static, inert image a lock and key conveys. Ehrlich had already concluded that that antibody and antigen might fit each other like a key in a lock (a metaphor borrowed from Emil Fischer 5 ).…”
Section: B Cell Toler An Ce In Three Dimens Ionsmentioning
confidence: 99%
“…The idea that the specificity of antibody and hence B cell recognition derives to a considerable extent from the three dimensional interaction of paratope and epitope traces to the lock and key model and that metaphor is still used to describe some antibody-antigen interactions. 6,7 Despite the heuristic appeal of the lock and key model, interactions between antibodies and antigens, particularly paratopes with epitopes, are far more complex than the static, inert image a lock and key conveys. The three dimensional structures of antibodies do appear to fit some antigens, but forces never imagined in the original model govern the rate and extent or association and the permanence of binding.…”
Section: B Cell Toler An Ce In Three Dimens Ionsmentioning
confidence: 99%